DOES THE CALCULATED DECAY CONSTANT FOR 7BE VARY SIGNIFICANTLY WITH CHEMICAL FORM AND/OR APPLIED PRESSURE? - Tossell J.A. (My University, 2002)
It has recently been reported that the electron capture decay constant for 7Be varies by as much as 1.5% in different oxidic compounds of Be and that application of 400 kbar pressure to a Be(OH)2 gel increases its 7Be decay constant by about 1%. Differences of such magnitude in decay rate might be useful in determining the speciation of Be in glasses, gels and aqueous solutions. We have recently calculated structures, 9Be NMR shieldings and IR/Raman spectra for both monomeric and oligomeric species of Be to assist in determining Be speciation. We here use similar methods to calculate the electron densities at the Be nucleus, which determine the rates of electron capture decay. We find that variations in the electron density at the Be nucleus in a number of oxidic compounds are only at the 0.1-0.4% level, as had been concluded in the 1970s. This raises doubts about the recent experimental results which show larger variations from one oxidic compound to another. The calculated 9Be NMR shifts of these species differ by only a few ppm, but such changes are readily measurable by NMR spectroscopy, and they depend systematically on the degree of hydrolysis and the degree of oligomerization. Rough estimates of the effects of Be-O bond compression in Be(OH)42- on the energy and the electron density at the nucleus indicate that several hundred kbar of pressure could increase the electron density by 1% or more, qualitatively consistent with the experimental results.
Keywords: BE-7; RADIOACTIVE DECAY; HIGH PRESSURE; ELECTRONS